Advantages and disadvantages of distance communication software - Kryvonos, I. O. (ТДАТУ, 2020)
We can conclude that the best online-platform for up-to-date young teachers is DISCORD. For elder lectures, it would be easier to use GOOGLE MEET service. And for those, who prefer functionality to simplicity, we propose to work with ADOBE CONNECT.
Keywords: distance learning; the format of studying; DISCORD; GOOGLE MEET